Legal Contradictions Regarding The Requirements for Establishing A Limited Liability Company Under Act No. 40 Of 2007 on Limited Liability Companies and Act No. 11 of 2020 on Job Creation and Their Implications for The Establishment of Microfinance Institutions - Dedy Nur Arifin (CV. Publikasi Indonesia, 2026)
This study examines the legal antinomy that arises between Article 7 paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies (Undang-Undang Perseroan Terbatas, UUPT), which requires the establishment of a company by a minimum of two people, and Article 153A paragraph (1) of Law Number 11 of 2020 concerning Job Creation (Undang-Undang Cipta Kerja, UUCK), which allows the establishment of an Individual Company by one person for micro and small businesses. Furthermore, this study analyses the implications of the conflict between these norms and the provisions of Article 2 paragraph (1) of the Financial Services Authority Regulation Number 41 of 2024 concerning Microfinance Institutions (Peraturan Otoritas Jasa Keuangan Lembaga Keuangan Mikro, POJK LKM), which regulates the establishment of a legal entity of Microfinance Institutions (MFIs) in the form of limited liability companies (Perseroan Terbatas, PT). This study uses a normative juridical method with a legislative approach and a conceptual approach. The results of the study show that there is a partial antinomy between the norms of the UUPT and the UUCK, where the provisions of the UUCK as lex posterior and lex specialis apply to the establishment of a company by micro and small business actors. With regard to MFIs, the provisions of POJK Number 41 of 2024 do open opportunities for MFIs to form PTs, but the application of Article 153A to MFIs requires the fulfilment of the criteria for micro and small businesses as stipulated in laws and regulations, so that not all MFIs in the form of PTs can be automatically established by one person.